Bacterial incidence and drug resistance from pathogens recovered from blood, cerebrospinal and pleural fluids in 2019–2020. Results of the Invifar network - Garza-González, Elvira; Camacho-Ortiz, Adrian; Ponce-de-Leon, Alfredo; Ortiz-Brizuela, Edgar; López-Jácome, Luis Esaú; Colin, Claudia; Rojas-Larios, Fabian; Newton-Sánchez, Oscar A.; Echaniz-Aviles, Gabriela; Carnalla-Barajas, Maria Noemi; Soto, Araceli; Bocanegra-Ibarias, Paola; et al. (PeerJ, 2023)
Background Antimicrobial resistance is a global concern. Analysis of sterile fluids is essential because microorganisms are defined as significant in most cases. Blood, cerebrospinal, and pleural fluids are frequently received in the microbiology lab because they are associated with considerable rates of morbi-mortality. Knowledge of epidemiology in these samples is needed to choose proper empirical treatments due to the importance of reducing selection pressure. Methods We used retrospective laboratory data of blood, CSF, and pleural fluid collected from patients in Mexico between 2019 and 2020. Each laboratory identified the strains and tested susceptibility using its routine methods. For Streptococcus pneumoniae, a comparative analysis was performed with data from the broth microdilution method. Results Forty-five centers participated in the study, with 30,746 clinical isolates from blood, 2,429 from pleural fluid, and 2,275 from CSF. For blood and CSF, Staphylococcus epidermidis was the most frequent. For blood, among gram negatives, the most frequent was Escherichia coli. Among Enterobacterales, 9.8% of K. pneumoniae were carbapenem-resistant. For S. pneumoniae, similar resistance percentages were observed for levofloxacin, cefotaxime, and vancomycin. For CSF, the most frequent gram-negative was E. coli. In Acinetobacter baumannii, carbapenem resistance was 71.4%. The most frequent species detected for pleural fluid was E. coli; in A. baumannii, carbapenem resistance was 96.3%. Conclusion Gram-negative bacteria, with E. coli most prevalent, are frequently recovered from CSF, blood, and pleural fluid. In S. pneumoniae, the routine, conventional methods showed good agreement in detecting resistance percentages for erythromycin, levofloxacin, and vancomycin.
Keywords: Drug resistance; Blood stream infection; Cerebrospinal infection; Escherichia coli; INVIFAR